2020
DOI: 10.1083/jcb.201911047
|View full text |Cite
|
Sign up to set email alerts
|

ULK complex organization in autophagy by a C-shaped FIP200 N-terminal domain dimer

Abstract: The autophagy-initiating human ULK complex consists of the kinase ULK1/2, FIP200, ATG13, and ATG101. Hydrogen-deuterium exchange mass spectrometry was used to map their mutual interactions. The N-terminal 640 residues (NTD) of FIP200 interact with the C-terminal IDR of ATG13. Mutations in these regions abolish their interaction. Negative stain EM and multiangle light scattering showed that FIP200 is a dimer, while a single molecule each of the other subunits is present. The FIP200NTD is flexible in the absence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 50 publications
9
72
0
Order By: Relevance
“…This phosphorylation is dependent on ULK1 and FIP200 ( Figure 4A, 4B and EV4), but not on ATG9A ( Figure 4B). Structural studies of FIP200 N-terminal domain show that it forms a dimer which interacts with only one molecule each of ATG13 and ULK1 (Shi et al, 2020). This peculiar interaction mode suggests that clustering of more FIP200 dimers is necessary to bring together ULK1 molecules, leading to their clustering and subsequent activation by autophosphorylation (Bach, Larance et al, 2011) and potentially protection from counteracting phosphatases.…”
Section: Fip200 Is Necessary For Ulk1 Activation At P62mentioning
confidence: 99%
See 1 more Smart Citation
“…This phosphorylation is dependent on ULK1 and FIP200 ( Figure 4A, 4B and EV4), but not on ATG9A ( Figure 4B). Structural studies of FIP200 N-terminal domain show that it forms a dimer which interacts with only one molecule each of ATG13 and ULK1 (Shi et al, 2020). This peculiar interaction mode suggests that clustering of more FIP200 dimers is necessary to bring together ULK1 molecules, leading to their clustering and subsequent activation by autophosphorylation (Bach, Larance et al, 2011) and potentially protection from counteracting phosphatases.…”
Section: Fip200 Is Necessary For Ulk1 Activation At P62mentioning
confidence: 99%
“…and it appeared as a cup-shaped structure by super-resolution microscopy (Kenny, Chen et al, 2019). Recently, electron microscopy analysis of purified ULK1-ATG13-FIP200 complex, revealed that the N-terminal domain of FIP200 forms a C-shaped scaffold which organizes the other subunits of the complex (Shi, Yokom et al, 2020). Here, we studied the selective autophagy process known as aggrephagy, mediated by the cargo receptor p62/SQSTM1.…”
mentioning
confidence: 96%
“…This suggests that Atg11 dimerization is supported primarily by a different interface. Recent work on FIP200, the mammalian analog of Atg11, demonstrated that the N-terminal region of FIP200 is a C shaped dimeric structure (Shi et al, 2020). If Atg11 contains a similar N-terminal region it may serve as the primary site of Atg11 dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…In Ara been identified, but how they function as regulatory and/or scaff and awaits future investigation [98]. [ On the contrary to the yeast Atg1 complex, structural information of the intact ULK1 complex in mammals has remained unexplored until a recent study reported the EM analysis of the complex [46]. The FIP200 N-terminal domain (NTD) was found to be a dimer.…”
Section: The Ulk1/atg1 Complexmentioning
confidence: 99%
“…Upon autophagy initiation, an isolated membrane known as the phagophore is formed at diverse membrane sites such as endoplasmic reticulum (ER) subdomains, mitochondria-ER contact sites, the ER-Golgi intermediate Despite extensive research over the past decades, our knowledge on the underlying molecular mechanisms of autophagosome biogenesis remains far from complete [76,77]. Recent studies using single-particle electron microscopy (EM) has contributed remarkable progress in the structural elucidation of several ATG proteins [46,67,73,78,79]. Here we focus on the structural biology aspect of the autophagosome biogenesis with emphasis on studies by single-particle EM and discussed the structure-function relationship of the core ATG proteins involved in autophagy initiation.…”
Section: Introductionmentioning
confidence: 99%